تخطيط تعليم اللغة العربية في معهد الجامعة والي سانجا سمارانج - Ghoniyah, Nushah Ziadatul (Tarbiyatuna: Jurnal Pendidikan Ilmiah, 2020)
Today, the pesantren tradition has been transformed with many variations. One of the variants is the phenomenon of pesantren in the university/campus or known as the student ma’had. One of pesantren in university is ma’had Al-Jami’ah Walisongo which is located in the UIN Walisongo campus in Semarang. The existence of this ma’had is expected to develop the students’ potential to have competence in the Arabic and English field. The things that will be discussed in this research are related to the planning of Arabic language learning. This type of research is qualitative research in the form of descriptive analysis with data sources in the form of documentation of the research results either scientific journals, etc. This study aims to find out about the learning planning from the aspects of how to formulate objectives, media, methods, teaching materials, and evaluation of Arabic learning. The results of this study are concluded in formulating learning objectives, it was adjusted to the vision and mission of ma’had Al-Jami’ah Walisongo. Teaching materials used are the book ’Silsilatun fî Ta’lîmi al-Lughati al-’Arabiyyah - al-’Arabiyyah Basîthah’, the learning media for the Ta’lim al-Lughah guidebook and its syllabies, generally the learning methods usedare drill and direct methods, and evaluation is conducted twice in odd and even semesters.